MICROSCOPIC USE-WEAR ANALYSIS: A Basic Introduction on How to Reconstruct the Functions of Stone Tools - Pawlik, Alfred F. (Hukay; Vol 3 No 1, 2014)
A Basic Introduction on How to Reconstruct the Functions of Stone Tools.